Organizational routines in university libraries in the context of the pandemic: a literature review - Graciosa, Maria Lidiane Herculano; Machado, Nelson Santos (Ciência da Informação em Revista, 2023)
The article aims to present the organizational routines in a university library and the occurrence of changes to deal with the pandemic. A bibliographical survey was carried out of the constructs of organizational routines, university library, remote work and studies carried out in Brazilian university libraries that contextualize the pandemic period. The review addressed the theory of organizational routines, its ostensive and performative aspects and artifacts, as well as concepts about the university library and the issue of remote work resulting from the covid-19 pandemic. The result showed the dynamics of organizational routines during the pandemic period, when libraries closed, however, services/products needed to be offered. Technological artifacts were protagonists in enabling interaction between actors and the provision of services. However, the moment was marked by the performative aspect, considering that library agents promoted actions that produced changes and innovation.